Christian Ethics. - Wogaman, J. Philip (Presbyterian Publishing Corporation, 2010)
An updated survey of Christian ethics which addresses major thinkers, movements, and issues from the early church to the present; and discusses a broad range of topics, including the biblical and philosophical legacies of Christian ethics and ethics through the early, medieval, Reformation, Enlightenment, and modern eras.